Numerical investigation on the utilization of phase change material (PCM) to reduce building's HVAC energy consumption - Nasif M.S.; Samsudin A.F.S.M.; Ismail F.B.; Lim D.C. (American Institute of Physics Inc., 2023)
The potential of utilization of PCM in storing energy through latent heat energy storage (LHTES) can be employed to provide free cooling. In this research, Phase Change Material (PCM) is used and coupled with Liquid to Air Membrane Energy Exchanger (LAMEE) and Underfloor Air Conditioning System to achieve thermal comfort of occupant by supplying cooled air into an office room. Computational Fluid Dynamics (CFD) simulation has been used to investigate the above system potential in provide thermal comfort instead of conventional air conditioning system by achieving the same thermal comfort. PCM coupled heat exchanger with the flat slabs and room office model have been constructed in this research. The heat gain inside and outside of the office room with the global position of Kuala Lumpur was included in the CFD simulation to illustrate the real environment. Humidity ratio of ambient air after passing through the LAMEE was included as the boundary inlet condition at the office room. It was found that the thermal comfort of occupant in an office room which are in the temperature between 21C - 24C and relative humidity of 40% - 60% can be achieved for duration of 1 hour and 30 minutes. 2018 Author(s).